Examination of the Questions Related to Exponential Expressions In 8th Grade Secondary School Mathematics Textbook and High School Transition Exam (Lgs) According to The Revised Bloom Taxonomy - Kadırhan, Dicle; Tanrıseven, Işıl (Atlas Journal, 2024)
Although high school transition systems vary from country to country, in many countries, high school entrance exams are used for students to transition to high school. These exams are important as they have a major impact on students' education and play a key role in determining their future career and academic goals. In Turkey, there are central exams such as Transition System from Basic Education to Secondary Education (TEOG), Secondary Education Institutions Examination (OKS) and finally Transition to High Schools Examination (LGS). In the High School Entrance Exams applied in our country since 2018, it is noteworthy that the average of Mathematics course has the lowest value among all courses. This situation makes it important to examine the mathematics questions that students encounter in the LGS exam and the questions in the textbooks they study. The aim of this study is to examine the knowledge and cognitive process dimensions of the Exponential Expressions study questions in the 8th grade mathematics textbook and the Exponential Expressions questions in LGS according to the Revised Bloom's Taxonomy (RBT). Thus, it is aimed to question the adequacy of textbooks in terms of preparing students for exams and achieving the objectives of the course. In line with this purpose, this study was designed as a document analysis research based on qualitative research method. Within the scope of the study, the 8th grade mathematics textbook prepared by the Ministry of National Education Board of Education (MEBTTK) for the 2023-2024 academic year and the LGS mathematics questions applied between 2017 and 2023 were analysed. An evaluation was made on 33 questions in the textbook and 14 questions in the LGS. According to the findings obtained from the study, it was concluded that the questions in the textbook were mostly in the conceptual knowledge dimension and at the comprehension stage, whereas the questions published in the LGS were mostly in the metacognitive knowledge dimension and at the evaluation and analysis stage.